2020
DOI: 10.15252/embr.201949831
|View full text |Cite
|
Sign up to set email alerts
|

A unique binding mode of Nek2A to the APC /C allows its ubiquitination during prometaphase

Abstract: The anaphase‐promoting complex (APC/C) is the key E3 ubiquitin ligase which directs mitotic progression and exit by catalysing the sequential ubiquitination of specific substrates. The activity of the APC/C in mitosis is restrained by the spindle assembly checkpoint (SAC), which coordinates chromosome segregation with the assembly of the mitotic spindle. The SAC effector is the mitotic checkpoint complex (MCC), which binds and inhibits the APC/C. It is incompletely understood how the APC/C switches substrate s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 53 publications
1
33
0
Order By: Relevance
“…Deep mutational scanning enabled systematic evaluation of the contribution for all residue possibilities within the LP cyclin motif ( 28 ). The cryo-EM ‘resolution revolution’ yielding structures of large macromolecular complexes is likely to be increasingly valuable in the future, especially for cases where the motif-binding interface involves more than one subunit on the binding partner, or when multiple motifs cooperatively bind to several subunits of a protein complex ( 92 ). Very recently, AlphaFold2 has been made available for protein structure prediction ( 93 ).…”
Section: Exploring Linear Motifsmentioning
confidence: 99%
“…Deep mutational scanning enabled systematic evaluation of the contribution for all residue possibilities within the LP cyclin motif ( 28 ). The cryo-EM ‘resolution revolution’ yielding structures of large macromolecular complexes is likely to be increasingly valuable in the future, especially for cases where the motif-binding interface involves more than one subunit on the binding partner, or when multiple motifs cooperatively bind to several subunits of a protein complex ( 92 ). Very recently, AlphaFold2 has been made available for protein structure prediction ( 93 ).…”
Section: Exploring Linear Motifsmentioning
confidence: 99%
“…In a structure of the APC/C-NEK2A complex (Alfieri et al, 2020), APC2 WHB is repositioned to the APC2-APC4 interface, similar to where we assign the SUMO-2 density (Figure S5E). In addition, our re-analysis of the APC/C in complex with the TAME inhibitor (an IR-tail mimic) (Zhang et al, 2016) also shows density for APC2 WHB at this site.…”
Section: Sumo-2 Binds To the Apc2-apc4 Subunit Interfacementioning
confidence: 55%
“…APC2 WHB emerges as a crucial and mobile element of the APC/C. Existing structures show that APC2 WHB is able to occupy four distinct sites: (1) its normal catalytic position when it interacts with the backside of UbcH10 ( Brown et al., 2015 ); (2) interaction with BubR1 of the MCC ( Alfieri et al., 2016 ; Yamaguchi et al., 2016 ); (3) interaction with APC10 described here; and (4) positioning at the APC2–APC4 interface ( Alfieri et al., 2020 ). In all of these instances, APC2 WHB plays a role in regulating APC/C activity during the SAC.…”
Section: Discussionmentioning
confidence: 90%
“…A recent study sought to determine how NEK2A binds APC/C MCC for ubiquitination during an active checkpoint by generating a high-resolution structure of NEK2A-APC/C MCC ( Alfieri et al, 2020 ). Through refinement of previously determined 3D models, Alfieri et al discovered that the CDC20 M IR tail dissociates from its APC8 binding site in the “open” APC/C MCC conformation ( Alfieri et al, 2016 ; Alfieri et al, 2020 ). This structural change would allow NEK2A to bind APC8 with its MR tail, in agreement with previous studies suggesting the importance of TPR-containing APC/C subunits ( Figure 4B ).…”
Section: Recent Studies Reveal How Certain Substrates Escape Mitotic mentioning
confidence: 99%
“…However, additional questions remain regarding interactions between these privileged substrates and E2 enzymes. It has been shown that NEK2A is more efficiently ubiquitinated by UBE2D than UBE2C, while the opposite is true for Cyclin A ( Zhang et al, 2019 ; Alfieri et al, 2020 ). Further structural studies are needed to fully characterize substrate-E2 combinations.…”
Section: Recent Studies Reveal How Certain Substrates Escape Mitotic mentioning
confidence: 99%